Kondisi Sosial Ekonomi Pekerja di Objek Wisata Pantai Dewi Mandapa Desa Gebang Pesawaran - Yudi Pratama; Sumadi Sumadi; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2017)
The objective of this research was aimed the social economic condition of family head who work at dewi mandapa beach tourism object in gebang village teluk pandan districts pesawaran regency. This research used the descriptive method. Population of this research many as 30 and all as respondent data. Data collectied by observation, questionnaire and documentation. Data analyzed by percentage for finishing] this research. The study result showed that: (1) giving the chance of jobs fot 30 peoples. (2) the income of 19 peoples was under the average. (3) the education of 23 peoples were basic educated of elementary and junior high school. (4) the number of children has 18 peoples. (5) 27 peoples as a home ownership. (6) working hours many as 21 peoples has the highest part time of work.Penelitian bertujuan mengetahui kondisi sosial ekonomi kepala keluarga yang bekerja di objek wisata pantai dewi mandapa desa gebang kecamatan teluk pandan kabupaten pesawaran. Metode penelitian yaitu metode deskriptif. Populasi penelitian 30 orang. Pengambilan data menggunakan observasi, kuesioner, dan dokumentasi. Analisis data menggunakan analisis persentase. Hasil penelitian menunjukkan: (1) memberikan kesempatan kerja sebanyak 30 orang. (2) pendapatan 19 orang dibawah rata-rata. (3) Pendidikan 23 orang masih pendidikan dasar SD dan SMP. (4). Jumlah tanggungan keluarga sedikit berjumlah 18 orang. (5) Status kepemilikan rumah 27 orang berstatus milik sendiri. (6) Jam kerja 21 orang memiliki jam kerja tinggiKata kunci: ekonomi, pekerja, sosial